Evaluation of 3-axis and 5-axis milling strategies when machining freeform surface features - Ižol, Peter; Varga, Ján; Vrabeľ, Marek; Demko, Michal; Greš, Miroslav (Journal of Production Engineering, 2022)
The article deals with the comparison and evaluation of milling strategies, which are available in CAM systems and are used for the production of components with freeform surfaces. For the purpose of the experiment a test sample with a repeating shape feature was designed. First half of the test sample shape features were machined using 3-Axis milling strategies while second half was performed with strategies available on 5-Axis CNC machining centre. Simulated machining times as well as virtually machined surfaces using color maps with deviation values were evaluated by employed CAM software. Obtained data was used to evaluate the performance of 3-Axis and 5-Axis milling centre both individually and mutually. These results will be used to compare software data with data obtained from real sample production. The main goal is to verify the reliability of the results provided by CAM systems in the production of parts with freeform.